2007
DOI: 10.1159/000103917
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Combination of Fenofibrate and Rosiglitazone in Pressure Overload-Induced Cardiac Hypertrophy in Rats

Abstract: The present study has been designed to investigate the effects of fenofibrate, a peroxisome proliferator-activated receptor (PPAR)α agonist, rosiglitazone, a PPARγ agonist and the combination of both fenofibrate and rosiglitazone in partial abdominal aortic constriction (PAAC)-induced pathological cardiac hypertrophy in rats. Rats were subjected to PAAC for 4 weeks to produce pathological cardiac hypertrophy. The fenofibrate (3 mg/kg day–1, p.o.), rosiglitazone (3 mg/kg day–1, p.o.) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 77 publications
(65 reference statements)
1
24
0
Order By: Relevance
“…In a model of arterial hypertension (DOCAsalt model), PPARα and PPARγ activation were both able to reduce cardiac fibrosis [14] . Similar effects were also observed in a pressure overload-induced cardiac hypertrophy, induced by partial constriction of the abdominal aorta [15] . In addition, PPARα/γ activation had anti-proliferative effects, antagonized angiotensin II actions in vivo and in vitro, and exerted antioxidant actions in inhibiting generation of reactive oxygen species and activating inflammatory mediators in blood vessels and the heart [16] .…”
Section: Introductionsupporting
confidence: 72%
“…In a model of arterial hypertension (DOCAsalt model), PPARα and PPARγ activation were both able to reduce cardiac fibrosis [14] . Similar effects were also observed in a pressure overload-induced cardiac hypertrophy, induced by partial constriction of the abdominal aorta [15] . In addition, PPARα/γ activation had anti-proliferative effects, antagonized angiotensin II actions in vivo and in vitro, and exerted antioxidant actions in inhibiting generation of reactive oxygen species and activating inflammatory mediators in blood vessels and the heart [16] .…”
Section: Introductionsupporting
confidence: 72%
“…16 On the other hand, other studies have concluded that the effects of fibrate treatment on cardiac hypertrophy were mostly positive. Fenofibrate successfully prevent cardiac hypertrophy in a number of in vivo animal models including: high-fat/high-sucrose dietinduced (Fernandes-Santos et al 2009), aldosterone-induced (Lebrasseur et al 2007), partial abdominal aortic constriction induced (Rose et al 2007) and pressure overloadinduced cardiac hypertrophy (Duhaney et al 2007). Our results suggest at least some beneficial effects by preventing LV dilatation, eccentric remodeling and preserving systolic function despite the absence of a clear anti-hypertrophic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrates are a class of hypolipemic drugs acting on PPARα activation. They have been shown in models of concentric hypertrophy due to pressure overload to have some anti-hypertrophic effects (Chen et al 2007;Diep et al 2004;Harvey et al 2011;Iglarz et al 2003;Lebrasseur et al 2007;Li et al 2009;Nishida et al 2004;Purushothaman et al 2011;Rose et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Fenofibrate not only prevents the development of hypertension and hypertensive heart disease (27), but also prevents the progression of cardiac hypertrophy either in the pressure-overloaded rat or in the spontaneously hypertensive rat (28,29). Moreover, fenofibrate was shown to protect the heart from isoproterenol-induced acute myocardial ischemic injury (30).…”
Section: Discussionmentioning
confidence: 99%